A NaHCO3 Promoted Three‐component Cyclization: Easy Access to Benzodisulfide Heterocycles. Issue 6 (12th May 2022) - Zhou, Yong‐Jun; Yang, Kai; Fang, Yong‐Gan; Luo, Shi‐He; Chen, Qi; Yu, Shi‐Wei; Wang, Zhao‐Yang
Abstract: A facile route for the synthesis of benzodisulfide heterocyclic compounds via a NaHCO3 ‐promoted three‐component reaction between 2‐halophenylacetic acids, elemental sulfur (S8 ) and amines under metal‐free conditions has been demonstrated. This transformation from available starting materials shows good functional group tolerance, and the target compounds can be derivatized for further application. Abstract : A transition metal‐free catalyzed cyclization reaction of 2‐halophenylacetic acid, aromatic amines and elemental sulfur was developed. This synthetic method successfully prepared a variety of benzodithio heterocyclic compounds in high yields via the promotion of simple inorganic base under mild reaction conditions.